The Effectiveness of Video as Media to Teach Procedure Text Writing at SMKN 1 Rejotangan - Vivi Alfiana Nuriyah; Moh. Hanafi (MultiTech Publisher, 2024)
The primary goal of learning English is to serve as a means of communication, given its status as a global language. It is crucial for educators to employ effective teaching techniques that pique students' interest in learning English. To achieve this, instructors should utilize appropriate approaches for instructing procedural writing to encourage active and creative participation in the classroom. Leveraging video as an educational tool aligns with the goals of language instruction, particularly when teaching writing especially write procedural texts. The researchers employed a quantitative research methodology to analyze the data collected in this study. The study focused on the population of class XI students at SMKN 1 Rejotangan with a sample of 41 eleventh-grade AKC 1 students. The research instruments included pre-test and post-test writing assessments. Data analysis involved descriptive statistical analysis and hypothesis testing utilizing the Wilcoxon test. The average score in the post-test was found to be higher than the initial test (53.8537 > 79.9024). Moreover, the obtained significant value was lower than the predetermined significance level (0.000 < 0.05), indicating a significant improvement in students' writing abilities after being taught using video as a media.